Child to Child Education Programme: A Model for overall Development of school going Students of Poorer Communities - Vaghela, Joyce Felicia; Wanjari, Pritee; Gupta, Vinita; Banerjee, Sayantan; Bahadur, Raj (Journal of Advanced Research in English & Education, 2021)
Quality education is the 4th goal of Sustainable Development Goals adopted by all United Nations Member States in 2015. ‘Child to Child approach’ is based on the idea of children working together with other children to bring about change. Child to Child Education Programme of Community Health Department of a tertiary care hospital was started in 1999 in a slum community. It provided a conducive-atmosphere to students. This has helped in promoting all-round development of children. The aim of this retrospective study is to show the effectiveness of this programme. Method: This retrospective study was conducted from 15th January 2020 to 31st March 2020, in a slum community of Delhi, for 11362 school going children, who have attended CCEd. programme between the years 1999 to 2019. The Secondary Data was collected. It was cleaned, and tabulated with frequency tables and percentages using MS-Excel. The significance and Odd’s ratio were calculated on MedCalc software. Results: Immediate impact of CCEd. on students was seen as the percentage of merit holders increased and was found to be between 5.23% – 13.26%. They were exposed to several Curricular, Extra-curricular, Social & Health Activities during the years they were part of CCEd. The qualifications of alumni of CCEd. programme showed that 116(76.31%) out of 152 are holding either a graduate degree or post graduates degree. The monthly income of alumni showed that a maximum number of alumni [36(23.68%)] earn Rs. 15000- 20000/ per month and some 6(3.95%) earn Rs. >45000-50000/- per month. They had always desired to be at par with other children/students of their age from privileged communities which they have attained in life. They are happy and satisfied. How to cite this article:  Vaghela JF, Wanjari P, Gupta V et al. Child to Child Education Programme: A Model for overall Development of school going Students of Poorer Communities J Adv Res Eng & Edu 2020; 5(1): 1-11. DOI: https://doi.org/10.24321/2456.4370.202001